2003
DOI: 10.1074/jbc.m304280200
|View full text |Cite
|
Sign up to set email alerts
|

The Different Large Subunit Isoforms of Arabidopsis thaliana ADP-glucose Pyrophosphorylase Confer Distinct Kinetic and Regulatory Properties to the Heterotetrameric Enzyme

Abstract: ADP-glucose pyrophosphorylase catalyzes the first and limiting step in starch biosynthesis and is allosterically regulated by the levels of 3-phosphoglycerate and phosphate in plants. ADP-glucose pyrophosphorylases from plants are heterotetramers composed of two types of subunits (small and large). In this study, the six Arabidopsis thaliana genes coding for ADP-glucose pyrophosphorylase isoforms (two small and four large subunits) have been cloned and expressed in an Escherichia coli mutant deficient in ADP-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
159
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 49 publications
18
159
1
Order By: Relevance
“…Previously, L subunits from group III (StuL, APL3, and APL4) were shown to have a regulatory function with a defective catalytic role (2,4,5,31,32). On the other hand, isoforms APL1 and APL2 (groups I and II) were catalytic with a critical role in regulation (2,5). The unicellular algae branches of the tree for S and L subunits have not been characterized (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, L subunits from group III (StuL, APL3, and APL4) were shown to have a regulatory function with a defective catalytic role (2,4,5,31,32). On the other hand, isoforms APL1 and APL2 (groups I and II) were catalytic with a critical role in regulation (2,5). The unicellular algae branches of the tree for S and L subunits have not been characterized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The L subunit from potato tuber (StuL) is catalytically deficient and plays more of a regulatory role by modifying the apparent affinity of the S subunit toward allosteric regulators (1,4). On the other hand, the Arabidopsis APL1 and APL2 isoforms have both catalytic and regulatory functions, whereas the APL3 and APL4 isoforms behave like StuL (2,5). The maize (Zea mays) endosperm L subunit has been postulated to have a role in catalysis due to effects on apparent affinity of substrates (6), but this may be explained by allosteric effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ADP-Glc pyrophosphorylases provide ADP-Glc for starch synthesis and can be divided into two clades, small (S) subunit and large (L) subunit clades. As reported for ADP-Glc pyrophosphorylase S1 of Arabidopsis, the S subunit plays a central role in the synthesis of ADP-Glc, whereas the L subunit has weak enzymatic activity and instead functions as regulatory protein to enhance the activity of the S subunits (Crevillén et al, 2003;Petreikov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the expressions of LS genes are usually tissue-and development-specific. The expression patterns and regulatory properties of different LS isoforms have been comprehensively studied in tomato (Park and Chung 1998), Arabidopsis (Crevillén et al 2003(Crevillén et al , 2005, and rice , and the results of those studies strongly indicate that AGPase heterotetramers formed in different tissues or organs display distinct kinetic and regulatory properties to control starch biosynthesis. It is suggested that the LSs of agriculturally important crops such as potato and tomato, which have undergone significant selection under both domestication and natural selection, may have evolved novel modulatory characteristics (Petreikov et al 2010).…”
Section: Introductionmentioning
confidence: 99%